2023
DOI: 10.1111/jace.19063
|View full text |Cite
|
Sign up to set email alerts
|

SiCN ceramics with controllable carbon nanomaterials for electromagnetic absorption performance

Abstract: Different kinds of carbon nanomaterials, free carbon (C free ), graphene, and Ncontaining graphene (NG), in single-source-precursors-derived SiCN ceramics, were in situ generated by modifying polysilazane with divinylbenzene, dopamine hydrochloride and melamine, respectively. Adjusting the carbon source brings phase structure and electromagnetic wave absorption (EMA) properties differences of SiCN/C ceramics. In situ C free enhances the EMA capacity of SiCN ceramics by improving their electrical conductivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…To achieve this, either increasing the proportion of microwave entering the material or enhancing the loss inside depends on EM parameters. Therefore, the study of absorbing materials is essentially to optimize the EM parameters of materials by adjusting their composition and structure, so as to enhance their absorption and loss effects on EM wave 57,58 . Figure 5 shows the real and imaginary parts of permeability and the tangent of the magnetic loss angle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve this, either increasing the proportion of microwave entering the material or enhancing the loss inside depends on EM parameters. Therefore, the study of absorbing materials is essentially to optimize the EM parameters of materials by adjusting their composition and structure, so as to enhance their absorption and loss effects on EM wave 57,58 . Figure 5 shows the real and imaginary parts of permeability and the tangent of the magnetic loss angle.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the study of absorbing materials is essentially to optimize the EM parameters of materials by adjusting their composition and structure, so as to enhance their absorption and loss effects on EM wave. 57,58 Figure 5 shows the real and imaginary parts of permeability and the tangent of the magnetic loss angle. The real part of the permeability (𝜇 ′ ) indicates storage capacity.…”
Section: Static Magnetic and Dielectric Propertiesmentioning
confidence: 99%
“…5,6,11 Compositionally, PDCs with increased levels of free carbon and dielectric phases have been developed through managing pyrolysis conditions, 12 and employing a molecular approach with carbon-rich or metal-containing precursors. [13][14][15][16][17] For example, Yu et al reported a silicon oxycarbide nanocomposite with carbon nanotubes and cobalt silicide via a single-sourceprecursor derived ceramic method. This approach leverages the interactive contributions of both dielectric and magnetic losses.…”
Section: Introductionmentioning
confidence: 99%